Assessment of Kinematics and Electromyography Following Arthroscopic Single‐Tendon Rotator Cuff Repair. Issue 5 (14th September 2016) - Fritz, Jessica M.; Inawat, Ryan R.; Slavens, Brooke A.; McGuire, John R.; Ziegler, Dean W.; Tarima, Sergey S.; Grindel, Steven I.; Harris, Gerald F.
Abstract: Background: The increasing demand for rotator cuff (RC) repair patients to return to work as soon as they are physically able has led to exploration of when this is feasible. Current guidelines from our orthopedic surgery clinic recommend a return to work at 9 weeks postoperation. To more fully define capacity to return to work, the current study was conducted using a unique series of quantitative tools. To date, no study has combined 3‐dimensional (3D) motion analysis with electromyography (EMG) assessment during activities of daily living (ADLs), including desk tasks, and commonly prescribed rehabilitation exercise. Objective: To apply a quantitative, validated upper extremity model to assess the kinematics and muscle activity of the shoulder following repair of the supraspinatus RC tendon compared to that in healthy shoulders. Design: A prospective, cross‐sectional comparison study. Setting: All participants were evaluated during a single session at the Medical College of Wisconsin Department of Orthopaedic Surgery's Motion Analysis Laboratory. Participants: Ten participants who were 9‐12 weeks post–operative repair of a supraspinatus RC tendon tear and 10 participants with healthy shoulders (HS) were evaluated. Methods: All participants were evaluated with 3D motion analysis using a validated upper extremity model and synchronized EMG. Data from the 2 groups were compared using multivariate Hotelling T 2 tests with post hoc analyses based on Welch t ‐tests. Main Outcome Measurements: Participants' thoracic and thoracohumeral joint kinematics, temporal‐spatial parameters, and RC muscle activity were measured by applying a quantitative upper extremity model during 10 ADLs and 3 rehabilitation exercises. These included tasks of hair combing, drinking, writing, computer mouse use, typing, calling, reaching to back pocket, pushing a door open, pulling a door closed, external rotation, internal rotation, and rowing. Results: There were significant differences of the thoracohumeral joint motion in only a few of the tested tasks: comb maximal flexion angle ( P = .004), pull door internal/external rotation range of motion ( P = .020), reach abduction/adduction range of motion ( P = .001), reach flexion/extension range of motion ( P = .001), reach extension minimal angle ( P = .025), active external rotation maximal angle ( P = .012), and active external rotation minimal angle ( P = .004). The thorax showed significantly different kinematics of maximal flexion angle during the call ( P = .011), mouse ( P = .007), and drink tasks ( P = .005) between the 2 groups. The EMG data analysis showed significantly increased subscapularis activity in the RC repair group during active external rotation. Conclusions: Although limited abduction was expected due to repair of the supraspinatus tendon, only a single ADL (reaching to back pocket) had a significantly reduced abduction range of motion. Thoracic motion was shown to be used as a compensatory strategy during seated ADLs. Less flexion of the thorax may create passive shoulder flexion at the thoracohumeral joint in efforts to avoid active flexion. The RC repair group participants were able to accomplish the ADLs within the same time frame and through thoracohumeral joint kinematics similar to those in the healthy shoulder group participants. In summary, this study presents a quantification of the effects of RC repair and rehabilitation on the ability to perform ADLs. It may also point to a need for increased rehabilitation focus on either regaining external rotation strength or range of motion following RC repair to enhance recovery and return to the workforce. Level of Evidence: III